Integrative-Innovative Leadership in Qur’anic Pesantren: A Case Study of Tholibul Qur’an Islamic Boarding School - `Ainina, Mutanafisah Qurrotu; Makruf, Imam; Mudofir, Mudofir (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Qur’anic pesantren are required to respond to the growing demand for formal education while maintaining Qur’anic traditions as the foundation of institutional identity. This study aims to analyze integrative innovative leadership in Qur’anic pesantren education at Tholibul Qur’an Islamic Boarding School. The study uses a qualitative approach with a descriptive case study design. Data were collected through semi-structured interviews with key informants, consisting of the foundation chairman and ustadz/ustadzah involved in the educational process, supported by document review and relevant literature. The data were analyzed thematically through data condensation, data display, and conclusion drawing. The findings show that integrative innovative leadership operates through four connected mechanisms. First, leaders respond to the aspirations of students’ parents who expect pesantren education to be connected with formal academic recognition. Second, institutional change is legitimized through deliberation between leaders and pesantren administrators. Third, formal education through MTs and MA becomes a strategy to expand the social and academic function of the pesantren. Fourth, Qur’anic traditions are maintained through memorization, Qur’anic learning, daily worship practices, dakwatul Qur’an, and character formation. This study contributes to Islamic educational leadership studies by showing that innovation in Qur’anic pesantren is not a shift from tradition to modernization, but an integrative process that connects social needs, institutional renewal, and the preservation of Islamic values.